2016
DOI: 10.1364/oe.24.023677
|View full text |Cite
|
Sign up to set email alerts
|

Nanoimprinted distributed feedback lasers of solution processed hybrid perovskites

Abstract: Hybrid perovskite materials have considerable potential for light emitting devices such as LEDs and lasers. We combine solution processed CH3NH3PbI3 perovskite with UV nanoimprinted polymer gratings to fabricate distributed feedback (DFB) lasers. The lead acetate deposition route is shown to be an effective method for fabricating low-loss waveguides (loss coefficient ~6 cm-1) and highly compatible with the polymer grating substrates. The nanoimprinted perovskite exhibited singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 28 publications
4
75
0
Order By: Relevance
“…A very recent breakthrough toward future application of lead halide perovskites to real lasers was reported by Brenner et al [25] that demonstrated, for the first time, ASE under continuous wave optical excitation at 532 nm in the temperature range 80-120 K, with a minimum threshold of 400 Wcm −2 in a phase stable triple cation non stoichiometric Cs 0.1 (MA 0.17 FA 0.83 ) 0.9 Pb 0.84 (I 0.84 Br 0.16 ) 2. 68 . At higher temperatures the active material degradation prevented to reach the ASE threshold.…”
Section: Perovskites Bulk Polycrystalline Thin Filmsmentioning
confidence: 99%
“…A very recent breakthrough toward future application of lead halide perovskites to real lasers was reported by Brenner et al [25] that demonstrated, for the first time, ASE under continuous wave optical excitation at 532 nm in the temperature range 80-120 K, with a minimum threshold of 400 Wcm −2 in a phase stable triple cation non stoichiometric Cs 0.1 (MA 0.17 FA 0.83 ) 0.9 Pb 0.84 (I 0.84 Br 0.16 ) 2. 68 . At higher temperatures the active material degradation prevented to reach the ASE threshold.…”
Section: Perovskites Bulk Polycrystalline Thin Filmsmentioning
confidence: 99%
“…Most of the following work on perovskite thin films concentrated on the workhorse composition for solar cells, methylammonium (CH 3 NH 3 /MA) lead (Pb) triiodide (I 3 ) that emits around 790 nm. Random lasers [18], whispering gallery mode lasers [19][20][21][22], distributed feedback lasers [23][24][25], vertical cavity lasers [26,27] and photonic crystals lasers have been demonstrated using this CH 3 NH 3 PbI 3 composition [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…UV‐NIL was used to fabricate the DFB gratings according to the previously reported works 32,33. The gratings were made on an EVG 620 photomask aligner with custom NIL tooling.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we demonstrate a simple and efficient “pick and place” method to combine wavelength scale DFB gratings with high‐quality sheet‐like organic single crystals. By assembling flexible single crystal sheets on top of polymer gratings produced with ultraviolet nanoimprint lithography (UV‐NIL),32,33 we fabricate single frequency lasers with emission wavelength controlled by the feedback gratings. The method was successfully applied to make lasers from different sheet‐like single crystal materials, and we relate the laser properties to the optical constants of the birefringent crystals.…”
Section: Figurementioning
confidence: 99%